Uniscape En-Route Seminars (diségno, 2017)
In 2016 the Uniscape En-Route Seminars, whose V edition was represented by the successful Landscape & Archeology conference, was held again in Italy; the conference has been promoted by the Centro Studi Vitruviani in Fano in collaboration with Università Politec- nica delle Marche in Ancona, Uniscape, Università degli Studi di Urbino, Dis- tretto Culturale Evoluto Flaminia Next One and the Municipalities of Fano, Fossombrone and Cagli.